2004
DOI: 10.1007/s10620-004-9572-5
|View full text |Cite
|
Sign up to set email alerts
|

Current GI Endoscope Disinfection and QA Practices

Abstract: High-level disinfection (HLD) of GI endoscopes is readily achieved when published guidelines are observed. Contamination is linked to breakdowns in accepted procedure. However, there is no recognized method of verifying adequacy of endoscope reprocessing in routine practice and no data regarding current quality assurance (QA) practice. Prior reports have demonstrated a wide variation in routine clinical practice of GI endoscopy HLD. The goal of this study was to determine current practice at regional endoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Similar data have been found in other studies: 61.0% of centers surveyed in the US reported that endoscopes were carried by hand and that only 26.0% used a container for transport to the reprocessing area (14) . Sealing the endoscope is recommended prior to the cleaning procedure in order to observe any leakage or escape of air from the endoscope and because the immersion in water or cleaning solution may damage the meter (16,17,23) .…”
Section: Discussionsupporting
confidence: 89%
“…Similar data have been found in other studies: 61.0% of centers surveyed in the US reported that endoscopes were carried by hand and that only 26.0% used a container for transport to the reprocessing area (14) . Sealing the endoscope is recommended prior to the cleaning procedure in order to observe any leakage or escape of air from the endoscope and because the immersion in water or cleaning solution may damage the meter (16,17,23) .…”
Section: Discussionsupporting
confidence: 89%
“…Some have argued that routine environmental sampling is expensive and of little value, and that it should be reserved for investigation of outbreaks [9]. However, others have proposed surveillance cultures as a mechanism for quality assurance [10,11,12 ]. In one recent study [13 ], surveillance cultures led to the identification of an automatic endoscope reprocessing unit contaminated with Pseudomonas species, which has been previously reported [14].…”
Section: Monitoring the Outcome Of Endoscope Cleaning And Disinfectionmentioning
confidence: 95%
“…In a 2004 survey of SGNA members at centers in the Mid-Atlantic states, compliance with published standards was, again, inconsistent, and there was wide variation in adherence to both global principles and specific steps of manual cleaning, highlevel disinfection, drying, and quality monitoring. 38 Most recently, in 2009, the CDC piloted an infection control audit tool during inspection of 68 ambulatory surgical centers in four states to assess adherence to recommended practices. 10 Adherence to recommendations for reprocessing of endoscopic equipment was not uniform in 28.4% of 67 ambulatory surgery centers.…”
Section: Gi Endoscope Reprocessingmentioning
confidence: 99%